THE DIMENSION OF THE CHANGE OF LAW VIEWED FROM THE PERSPECTIVE OF OPEN LEGAL SYSTEM - Yuddin Chandra Nan Arif (Fakultas Hukum Universitas Mataram, 2013)
Law, as an open system, is a sort of a breakthrough as a field of study, enabling the creation of tolerance with other elements, which are outside of its scope. Consequently, law becomes a domain studied by other disciplines in the multidisciplinary context. Based on the foregoing, the significance of law as an open domain lies in its ability to introduce flexibility in legal rules, the reflexibility of which, along with the parallel social changes taking place, are likely to result in a legal reality which is responsive to the existing social realities. Law, as a unit of norms dealing with the recht object, namely society, must be open to development at all times. Law should not be static at one point, thus causing the life of the community to become constant. Law will always follow the developments taking place in society. As a platform for fundamental change which can be simply explained in the context of legal change and social change created in the process of integrating the human agency (identity and regularities) and the process of social change into the legal analysis, in terms of substance, structure, culture or all of these three within the legal system. At the level of an open legal system, the factor of change, whether its intended purpose is to adjust to the norms, or not to adjust to the requirements set by norms, are two variable motives, whereby the role occupant (person addressed by the law) is not aware of the norms concerned, or he/she is aware of such norms, however they do not suit the determined objectives. Therefore, there is a great need for interaction between legal change and social change in the context of the national legal reform which genuinely puts forward Indonesian values.Keywords: Legal Change, Social Change, Open Legal System.